2016
DOI: 10.5152/tud.2016.12369
|View full text |Cite
|
Sign up to set email alerts
|

Robotic kidney transplantation: The Bakırköy experience

Abstract: Objective: Robotic kidney transplantation, first described by Hoznek and colleagues, and has been improved by investigators like Oberholzer and Menon. We realized the first robotic kidney transplant (RKT) in our clinic in December 2015. In this study, we aimed to present the first 15 cases we performed within 3 months. Materıal and methods:Starting from January 2016, we performed 15 RKTs in our hospital. Before surgery, the whole robotic procedure was thoroughly explained to the patients and their informed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Even though it has been confirmed by other authors that this technique is safe and effective [8,18], many concerns remain regarding local and possibly systemic complications related to the use of intraperitoneal cooling to maintain the graft at a constant low temperature. Tu gcu et al [19] reported paralytic ileus as a complication of the use of ice slush, and no ileus occurred when the amount of ice slush was decreased. The three cases of ileus (2.5%) that we observed could also have been caused by intraperitoneal ice cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it has been confirmed by other authors that this technique is safe and effective [8,18], many concerns remain regarding local and possibly systemic complications related to the use of intraperitoneal cooling to maintain the graft at a constant low temperature. Tu gcu et al [19] reported paralytic ileus as a complication of the use of ice slush, and no ileus occurred when the amount of ice slush was decreased. The three cases of ileus (2.5%) that we observed could also have been caused by intraperitoneal ice cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there have been various publications of RAKT series. Studies carried out by Tuğcu et al and Breda et al are two examples that deal with RAKT in general. However, to the best of our knowledge there may be few, if any, studies that have compared RAKT with OKT.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail previously , in the RAKT technique, the patient is placed in a 15–30 ° supine Trendelenburg position. A 5‐cm paraumbilical incision is made for the placement of a gel port.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The RAKT technique was described by Hoznek et al and further developed by Oberholzer et al and Menon et al [10][11][12] Since then, favourable outcomes have been achieved in several transplant centres. [10][11][12]23,24 The European Robotic Urological Society (ERUS)-RAKT group has reported that RAKT is a safe and effective treatment option in the hands of surgeons experienced in robotic surgery and OKT. 25 In this study, they recommended cadaveric RAKT courses and mentor-guided surgery at the beginning of the learning curve.…”
Section: Discussionmentioning
confidence: 99%